Seeing above the clouds with high-resolution spectroscopy. Issue 1 (29th August 2020) - Gandhi, Siddharth; Brogi, Matteo; Webb, Rebecca K
ABSTRACT: In the last decade, ground-based high-resolution Doppler spectroscopy (HRS) has detected numerous species in transiting and non-transiting hot Jupiters, and is ideally placed for atmospheric characterization of warm Neptunes and super Earths. Many of these cooler and smaller exoplanets have shown cloudy atmospheres from low-resolution near-infrared observations, making constraints on chemical species difficult. We investigate how HRS can improve on these given its sensitivity to spectral line cores which probe higher altitudes above the clouds. We model transmission spectra for the warm Neptune GJ 3470b and determine the detectability of H2 O with the CARMENES, GIANO, and SPIRou spectrographs. We also model a grid of spectra for another warm Neptune, GJ 436b, over a range of cloud-top pressure and H2 O abundance. We show H2 O is detectable for both planets with modest observational time and that the high H2 O abundance-high cloud deck degeneracy is broken with HRS. However, meaningful constraints on abundance and cloud-top pressure are only possible in the high-metallicity scenario. We also show that detections of CH4 and NH3 are possible from cloudy models of GJ 436b. Lastly, we show how the presence of the Earth's transmission spectrum hinders the detection of H2 O for the most cloudy scenarios given that telluric absorption overlaps with the strongest H2 O features. The constraints possible with HRS on the molecular species can be used for compositional analysis and to study the chemical diversity of such planets in the future.